Learning Analytics Among University Teachers: Preliminary Findings - Marolt, Marjeta; Jakšić, Danijela; Slavuj, Vanja; Žnidaršič Mohorič, Anja (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This study investigates the use of learning analytics among university teachers. A survey, developed based on a literature review, was distributed to faculty members at the University of Maribor, Slovenia, and the University of Rijeka, Croatia. The preliminary findings show that university teachers primarily use learning management systems to collect data, but rarely combine data from different sources or use advanced analytics techniques such as machine learning. The study also reveals scepticism around ease of use, confidence in analytics and social impact, highlighting the importance of facilitating conditions for adoption. Despite these challenges, participants recognise the benefits of learning analytics to make informed decisions and improve teaching effectiveness. The study underscores the need for further research to develop better tools and support for widespread adoption.